Neurolinguistic Relativity: How Language Flexes Human Perception and Cognition. Issue 3 (19th June 2016) - Thierry, Guillaume
Abstract : The time has come, perhaps, to go beyond merely acknowledging that language is a core manifestation of the workings of the human mind and that it relates interactively to all aspects of thinking. The issue, thus, is not to decide whether language and human thought may be ineluctably linked (they just are), but rather to determine what the characteristics of this relationship may be and to understand how language influences—and may be influenced by—nonverbal information processing. In an attempt to demystify linguistic relativity, I review neurolinguistic studies from our research group showing a link between linguistic distinctions and perceptual or conceptual processing. On the basis of empirical evidence showing effects of terminology on perception, language‐idiosyncratic relationships in semantic memory, grammatical skewing of event conceptualization, and unconscious modulation of executive functioning by verbal input, I advocate a neurofunctional approach through which we can systematically explore how languages shape human thought.